The Effect of Jamboree Strategy on Respondents' Knowledge of Prevention of Drug Abuse Before and After Intervention in Junior High School 2 Purba Kinalang, Simalungun Regency - Venni Yuasnita R. Damanik; Kintoko Rochadi; Linda T (Britain International of Exact Sciences (BIoEx) Journal, 2020)
This study aims to determine the effect of jamboree strategy on respondents' knowledge of prevention of drug abuse before and after intervention in junior high school 2 Purba Kinalang, Simalungun Regency. The research design that the researchers will do is one group pre-test post-test design which will be conducted in the first week of pre-test and the second week is treated through health education by health workers and the third week will be carried out post-test to determine the effect of health education on treatment groups in increasing adolescent knowledge and attitudes about drugs. The conclusion of this study consists of several points, there were: Frequency distribution of the general characteristics of respondents, the majority of respondents are aged between 12-13 years, as many as 58.1% and as many as 53.2% of female (33 people). Knowledge of respondents before being given a jamboree strategy the majority of adolescents were less good at 82.3%. However, after being given a teenage jamboree strategy, the majority of respondents' knowledge was good at 64.5%. Thus there was a change of knowledge after being given the intervention of teenage jamboree.